Prognostic role of preoperative lymphocyte/C-reactive protein associated with upper gastrointestinal cancer: a meta-analysis - Ye, Yongjuan; Wu, Guozhi; Yuan, Hao; Zheng, Ya; Wang, Yuping; Guo, Qinghong (Frontiers in Oncology, 2023)
The lymphocyte/C-reactive protein (LCR) is a novel immunoinflammatory score and prognostic marker, but the relationship between lymphocyte/C-reactive proteins and clinical outcomes in patients with upper gastrointestinal cancers remains controversial. This study aimed to evaluate the relationship between LCR and the prognosis of upper gastrointestinal cancer by systematic evaluation and meta-analysis.We systematically searched PubMed, EMBASE, Cochrane, and Web of Science databases to obtain related studies on the relationship between LCR and esophageal cancer (EC), gastric cancer (GC), and esophagogastric junction cancers (EGJ), and used hazard ratio (HR), 95% confidence interval (95%CI) to evaluate the prognostic value of LCR. Outcome measures included overall survival (OS) and disease-free survival (DFS).Eight retrospective cohort studies with 2838 patients were included. Meta-analysis showed that patients with low LCR cancers had poor overall survival OS and disease-free survival DFS (HR=2.18, HR=1.88,). Subgroup analysis based on cancer type, treatment modality, gender, T stage, TNM stage, country, and LCR threshold showed that lower LCR levels were all associated with worse OS and DFS (P<0.05).The LCR can be used as a prognostic marker for patients with upper gastrointestinal cancers, and patients with a lower LCR may have a poor prognosis. Due to the limited number of studies included and mostly retrospective studies, the above findings require validation by more high-quality studies.